2004
DOI: 10.1242/dev.01155
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage tracing duringXenopustail regeneration

Abstract: The tail of the Xenopus tadpole will regenerate following amputation, and all three of the main axial structures – the spinal cord, the notochord and the segmented myotomes – are found in the regenerated tail. We have investigated the cellular origin of each of these three tissue types during regeneration.We produced Xenopus laevis embryos transgenic for the CMV (Simian Cytomegalovirus) promoter driving GFP (Green Fluorescent Protein) ubiquitously throughout the embryo. Single tissues were then specifically la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
196
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(203 citation statements)
references
References 30 publications
7
196
0
Order By: Relevance
“…Therefore, we analysed stage 54 limbs (staging according to Nieuwkoop & Faber [38]), which lay halfway in between the two extremes, i.e., they are not too immature and still regenerate to some extent. Tail amputations were used as a negative control for muscle dedifferentiation, as it was shown by Gargioli & Slack that tail muscle fibres do not contribute to the regenerate [8]. Surprisingly, we observed a dedifferentiation phenotype in the tail (Figure 3a-j), mainly at 3 days post-amputation (dpa).…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…Therefore, we analysed stage 54 limbs (staging according to Nieuwkoop & Faber [38]), which lay halfway in between the two extremes, i.e., they are not too immature and still regenerate to some extent. Tail amputations were used as a negative control for muscle dedifferentiation, as it was shown by Gargioli & Slack that tail muscle fibres do not contribute to the regenerate [8]. Surprisingly, we observed a dedifferentiation phenotype in the tail (Figure 3a-j), mainly at 3 days post-amputation (dpa).…”
Section: Resultsmentioning
confidence: 62%
“…We first confirmed that the alpha-cardiac actin (Car) promoter was able to drive strong and specific GFP expression in muscle fibres of the limb and tail (Figure 1a-c) [29]. However, these simple Car-GFP transgenics are not useful for cell tracing experiments, since the unlabeled myogenic progenitors activate GFP expression during regeneration and become indistinguishable from any possible unicellular fragments derived from labelled dedifferentiating myofibres (Figure 1d, arrows) [8]. …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations